Synthesis of Functionalized Magnetic Graphene Oxide by Iminodiacetic Acid to Remove Chromium from Contaminated Waters - Mahmoud Zarei; Salar Maleki; Mehdi Hosseinzadeh (آب و فاضلاب, 2023)
To remove pollutants, many methods have been used so far, including ion exchange, coagulation and reverse osmosis. Most of these methods have many disadvantages and among them, the adsorption method is considered as a useful method. The purpose of this study is to synthesize adsorbents in the form of nanocomposites based on graphene oxide and modify the surface of graphene oxide by using iminodiacetic acid ligand to remove chromium ion by adsorption method. To determine the chemical structure and characterization of functionalized magnetic graphene oxide, we used XRD, BET, FTIR and SEM analysis. After that, the factors affecting the removal rate such as adsorbent amount, time of reaction, pH and initial concentration of chromium ion were investigated. The optimal conditions for removal of chromium ion were obtained as pH of solution 2, initial adsorbent weight 30 mg, initial chromium ion concentration 15 mg/L, absorption process time of 15 minutes and removal efficiency was 92.00%. The experimental results and the results of the response surface design were in good agreement (98.8%). Reviewing kinetic and isotherm studies showed that the adsorption process follows the pseudo second-order kinetics and Langmuir isotherm. Magnetic graphene oxide functionalized with iminodiacetic acid has the highest adsorption rate and was considered as the optimal adsorbent for successful metal removal.